Electronic structure and dosage correlation of 1,4-benzodiazepines - Massoud, Raghdaa Adel; Makhyoun, Mohamed Abdalla (European Journal of Chemistry, 2019)
Density functional theory was used to calculate the electronic structure of 20 selected 1,4-benzodiazepine derivatives. Certain parameters were extracted from the theoretical calculations, including the proton affinity of N1, the total energy, HOMO and LUMO energies, the total positive atomic charge, dipole moment and molecular volume. These parameters were used for the correlation with the minimum effective dose acting on human. The correlation was performed by applying linear least square method. Seven parameters were found to afford good fit. Clorazepate, one of the benzodiazepines, was studied extensively, it contains a carboxylate group, which can act as an ordinary molecule or zwitterions, where the ionisable proton migrates to N1. The energy gap between the two forms was found to be strongly dependent on the solvent dielectric constant.